Haemostatic Variables and the Outcome of Myocardial Infarction - Haines, A P; Howarth, D; North, W R S; Goldenberg, Eva; Stirling, Yvonne; Meade, T W; Raftery, E B; Millar Craig, M W (Thrombosis and Haemostasis, 1983)
In a study of 272 patients with myocardial infarction (MI) the 68 who died within 1 year had significantly higher levels of factor VIIIR:Ag, factor VIII:C, fibrinogen, α1 antitrypsin and α2 macroglobulin than those who survived. The mean white cell count (WCC) and peak creatine kinase (CK) were also significantly higher in those who died compared with the survivors. There was considerable intercorrelation between many of the haemostatic variables, WCC and CK as well as between many of the clinical predictors of outcome and the laboratory variables. The differences in haemostatic variables between those who died and those who survived may merely reflect the size of the infarct; alternatively, the haemostatic system may influence prognosis following an MI.
Keywords: Myocardial infarction; Prognosis; Coagulation